OPTIMALISASI MANAJEMEN DIABETES MELLITUS MELALUI EDUKASI KESEHATAN BERBASIS KOMUNITAS DAN PENDEKATAN SPIRITUAL - Bistara, Difran Nobel; Setiawan, Arif Helmi; Ikwan, Mochamad; Savitri, Ardyarini Dyah; Susanti, Susanti (PPM STIKES Adi Husada, 2025)
Introduction & Aim: Diabetes Mellitus (DM) is a chronic disease with increasing prevalence, including in Wonokromo Village, Surabaya, where high-risk factors such as unhealthy eating patterns and low physical activity are common. Spiritual approaches and community-based health education are expected to improve DM management and patients' quality of life. This study aims to optimize DM management through spiritual approaches and community-based health education. Method: The activity was conducted with a participatory community-based approach, involving 85 participants diagnosed with DM or at high risk. The intervention included interactive health education on DM management, spiritual approaches through reflection and prayers, and capacity building for health cadres. Evaluation was done by measuring blood sugar levels and post-tests to assess knowledge improvement and behavioral changes. Results: The results showed that 90% of participants adopted a healthy lifestyle after the education, and 75% felt more motivated to take care of themselves. Additionally, 85% of members of the “Sahabat Sehat Diabetes” community actively participated in the activities, and 100% of cadres were able to conduct early detection and self-management education for DM. Discussion: Continuous health education, spiritual approaches, and social support enhancement proved effective in improving participants' knowledge, motivation, and medication adherence. The capacity building of health cadres is key to the sustainability of this program, which can be expanded to the wider community.